Youth entrepreneurship in Kazakhstan’s tourism: Potential and incentives for innovation - Aizhan Tleuberdinova; Nailya Nurlanova; Arailym Shokhamanova; Farida Alzhanova; Dinara Salauatova (Problems and Perspectives in Management)
Type of the article: Research Article Abstract Youth tourism entrepreneurship is a driver of sectoral development, reduces unemployment and poverty, and is a catalyst for innovation. The aim of this paper is to explore the potential of youth entrepreneurship in tourism, assess its impact on the development of Kazakhstan’s tourism industry, and formulate recommendations for fostering innovation. A systematic approach was adopted, employing methods of logical analysis, correlation and regression analysis, synthesis, and data visualization. Between August and December 2024, a survey was administered across 20 regions of Kazakhstan to assess young people’s readiness for tourism entrepreneurship, identify barriers to its development, and explore innovative solutions. The questionnaire was hosted on Google Forms and disseminated via social media, ensuring all responses remained anonymous. With 601 respondents, the sample is sufficiently representative of the Kazakhstani population aged 18 to 35 years.Covering the 2013–2023 period, the correlation and regression analysis revealed that youth tourism entrepreneurship has undergone dynamic growth and positively influenced Kazakhstan’s socio-economic indicators and tourism sector performance. Survey findings indicate a strong willingness among young people to engage in training and introduce innovations in tourism. Corruption and high taxation were identified as the principal obstacles to realizing entrepreneurial potential and advancing innovation. The study concludes that youth tourism entrepreneurship is vital for Kazakhstan’s economic diversification and innovation agenda. Involving young people in the tourism sector contributes to unemployment reduction. Regional disparities in resource access can be narrowed through targeted adjustments to state policies that support youth innovative entrepreneurship. Acknowledgments This study is supported by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan through the project AP 26199455 – “Entrepreneurial Motivation as a Factor for Economic Diversification in Regions: Sociocultural Prerequisites, New Directions, and Implementation Methods.”